Synthesis of organophosphates starting from α-hydroxyphosphonates. (27th May 2019) - Kiss, Nóra Z.; Rádai, Zita; Szabó, Réka; Aichi, Youness; Laasri, Laila; Sebti, Said
Abstract: α-Hydroxyphosphonates were successfully converted to the corresponding phosphates applying the phospha-Brook rearrangement under phase transfer catalytic conditions. Among several possible catalysts tested, K2 CO3, Cs2 CO3, as well as modified Moroccan phosphates were found to be suitable. Graphical Abstract: uf0001